The Existence of Customary Law as a Living Law within Indonesia’s Legal System: A Legal Pluralism Analysis - Theresia N.A Narwadan (PT. Anagata Sembagi Education, 2025)
This study analyzes the existence of customary law as a living law within Indonesia’s legal system through the paradigm of legal pluralism. Although Indonesia adopts a codified national legal system, customary law continues to function as a normative authority that regulates community behavior and dispute resolution. Using a normative juridical method supported by doctrinal analysis, this research reveals that the interaction between statutory law and customary law is characterized by philosophical and functional differences that frequently produce normative conflicts, particularly in land regulation, community sanctions and criminal justice. The findings indicate that effective harmonization requires a clear doctrinal placement of customary law within the national hierarchy, in which customary law governs culturally embedded communal affairs while statutory law prevails in constitutional and criminal matters. This structured pluralism model ensures legal certainty while preserving cultural identity. The study concludes that balanced normative coexistence is necessary to strengthen both legal legitimacy and cultural justice in Indonesia